Construction of the Training Model for Intercultural Communicative Competence in College English Teaching - Yue, Shuzhen (Journal of Research in Vocational Education, 2025)
Against the backdrop of globalization and deepening international exchanges, intercultural communicative competence (ICC) has become a core literacy requirement for college students in the new era, and integrating ICC cultivation into college English teaching has become an inevitable trend in the reform of English language education. This study, rooted in the researcher’s background in translation studies, years of college English teaching experience, and research focus on intercultural communication and communication studies, aims to address the current shortcomings in college English teaching—such as overemphasis on linguistic proficiency while neglecting cultural awareness, disconnected teaching content from real intercultural scenarios, and single-mode teaching methods. By adopting a mixed research method combining literature analysis, teaching case studies, and questionnaire surveys, this study first clarifies the connotation and structural dimensions of ICC based on recent interdisciplinary theories (including cross-cultural communication, translation studies, and second language acquisition). It then explores the intrinsic connections between translation practice, college English teaching, and intercultural communication: translation, as a “cultural mediator,” can effectively enhance students’ cultural sensitivity and contextual adaptation; teaching experience provides practical insights for designing student-centered activities; and intercultural communication theories offer a theoretical framework for optimizing teaching content. On this basis, the study constructs a “three-dimensional integration” ICC training model with “goal orientation, content integration, method innovation, and evaluation guarantee” as its core. The model takes “developing linguistic proficiency + cultural cognition + communicative strategies + cultural empathy” as the overall goal, integrates cultural content into language teaching through translation tasks (e.g., translating culturally-loaded texts), adopts diversified teaching methods (case analysis, intercultural simulation, project-based learning), and establishes a dual evaluation system combining formative and summative assessment. To verify the model’s effectiveness, a 16-week teaching practice was conducted at Liaoning University of International Business and Economics, involving 240 non-English major sophomores. The results show that students in the experimental group demonstrated significant improvements in cultural awareness (e.g., recognizing cultural differences in discourse), intercultural communication confidence, and the ability to handle cultural conflicts in translation compared to the control group. This study enriches the theoretical research on ICC cultivation in college English teaching by integrating translation studies and communication theories. Practically, it provides an operable teaching framework for colleges and universities, especially those with translation programs, to promote students’ comprehensive English literacy and meet the social demand for intercultural talents.